A consistent tapered beam-column element allowing for different variations and initial imperfections. (October 2021) - Chen, Wen-Feng; Liu, Yao-Peng; Du, Zuo-Lei; Bai, Rui; Chan, Siu-Lai
Abstract: In this paper, a new consistent analytical model is proposed for second-order direct analysis of steel structures with tapered members allowing for both symmetric and asymmetric variations. The proposed model is implemented in a flexibility-based beam-column element with considering initial geometrical imperfections at the element level. To account for the influence of varied tapering ratios on the member behavior, a new initial geometrical imperfection pattern is introduced for both prismatic and non-prismatic members using common section shapes such as I-shape, Tee-shape, circular and rectangular hollow sections. Note that the conventional bow imperfection pattern that is widely accepted for prismatic members may lead to unsafe design when it is adopted for the tapered members. Furthermore, residual stress is explicitly considered through a fiber section approach in the proposed beam-column element. Consequently, the traditional effective length method is no longer required, as both geometrical imperfections and residual stress have been taken into account. The progressive yielding behavior of tapered members is also considered through the fiber section with nonlinear stress–strain relationships. Thus, a comprehensive second-order direct analysis method is proposed for safer and more economical design of tapered structures without the assumption of the effective length factor for a stability check. Several numerical examples are employed to verify the accuracy and practicability of the proposed model.